What's in a name: the effect of category labels on teachers' beliefs. Issue 1 (1st January 2020) - Gibbs, Simon; Beckmann, Jens F.; Elliott, Julian; Metsäpelto, Riitta-Leena; Vehkakoski, Tanja; Aro, Mikko
ABSTRACT: In this paper, we report an investigation of the possible influence on teachers' essentialist thinking and efficacy beliefs of category labels used to describe children's educational difficulties. A 2x2x2 counterbalanced design was employed in which primary school teachers in Finland and the UK were exposed to vignettes that portrayed a child exhibiting difficulties in one of two domains: either behaviour or reading. Vignettes were presented in two versions. In one, the child was labelled as having either 'ADHD' or 'Dyslexia'; in the alternate condition, no such label was ascribed, descriptions were identical in all other respects. Participating teachers were presented with two vignettes, one from each domain and in each condition. Responses to measures of Efficacy and Essentialist beliefs were solicited. Overall responses indicated that category labels evoked stronger essentialist beliefs but did not influence teachers' efficacy beliefs. Finnish teachers reported stronger essentialist and lower efficacy beliefs than their counterparts in the UK.